2009
DOI: 10.1111/j.1365-2990.2009.01015.x
|View full text |Cite
|
Sign up to set email alerts
|

Spinocerebellar ataxia type 6 (SCA6): neurodegeneration goes beyond the known brain predilection sites

Abstract: In view of the known functional role of affected central nervous grey components it is likely that their degeneration at least in part is responsible for the occurrence of a variety of SCA6 disease symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 54 publications
5
29
0
Order By: Relevance
“…1 However, there is increasing evidence of a widespread affection of extracerebellar structures in SCA6, such as the thalamus, midbrain, and even the brain stem as shown by recent postmortem studies. 12,13 In the current volumetric MR imaging study, we found significant atrophy not only of the cerebellum but also of the brain stem in SCA6. Both cerebellar atrophy and brain stem atrophy contributed independently to the variance in clinical dysfunction in patients with SCA6.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…1 However, there is increasing evidence of a widespread affection of extracerebellar structures in SCA6, such as the thalamus, midbrain, and even the brain stem as shown by recent postmortem studies. 12,13 In the current volumetric MR imaging study, we found significant atrophy not only of the cerebellum but also of the brain stem in SCA6. Both cerebellar atrophy and brain stem atrophy contributed independently to the variance in clinical dysfunction in patients with SCA6.…”
Section: Discussionmentioning
confidence: 73%
“…In SCA6, Gierga et al 13 found, in a postmortem study, that the extent of brain stem neurodegeneration correlated with the age at disease onset and disease duration. Their interpretation was that the severity of degeneration in SCA6 might be determined by these 2 factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Symmetrical stimulation of the posterior semicircular canals with nystagmus frequency (CC=9 and C=9) with DP of 0%. Symmetrical stimulation of posterior semicircular canals, with nystagmus frequency (CC= 9 and C=9) with DP of 0%, and post-caloric nystagmus with air at 42ºC in the right ear (RE) with SCAV of 0°/s (no response), 42ºC in the left ear (LE) with SCAV of 18°/s, 18°C in RE cerebellar cortex and a gliosis of the inferior olivary complex [10][11][12] .…”
Section: Resultsmentioning
confidence: 99%